Human acellular dermis increases surgical site infection and overall complication profile when compared with submuscular breast reconstruction: An updated meta-analysis incorporating new products✰. Issue 11 (November 2018) - Smith, J. Michael; Broyles, Justin M.; Guo, Ying; Tuffaha, Sami H.; Mathes, David; Sacks, Justin M.
Abstract: Background: Human acellular dermal matrix (HADM) is an increasingly used adjunct to breast reconstruction. Previous meta-analyses demonstrate increased risks of complications, but these studies largely represent one product. The purpose of this study is to stratify outcomes on the basis of a meta-analysis of complications incorporating all new studies after 2012 and their associated new human-based products. Methods: A query of the MEDLINE database for articles on HADM and breast reconstruction from January 2012 to October 2015 yielded 172 citations. Two levels of screening identified 47 relevant studies. Thirteen studies were used in comparative meta-analysis. Results: Complication rates were higher in HADM patients: total complications, 17.7% versus 6.1%; seroma, 8.3% versus 5.4%; infection, 7.2% versus 5.9%; and flap necrosis, 14.7% versus 7.1%. Meta-analysis revealed a statistically significant increased risk of total complications in patients who underwent reconstruction with HADM when compared with their submuscular reconstruction cohort ( p = 0.03; relative risk (RR) = 1.46; confidence interval (CI): 1.04–2.04). Patients who underwent reconstruction with HADM demonstrated a significantly increased risk of flap necrosis ( p < 0.01; RR = 2.39; CI: 1.8–3.16) and infection ( p = 0.02; RR = 1.5; CI: 1.07–2.09) when compared with those who underwent submuscular reconstruction. There was no significant difference in seroma, hematoma, or implant explantation between these two groups. Conclusions: This study suggests an increased risk of overall complications, specifically infection and flap necrosis, in patients who underwent tissue expander/implant breast reconstruction with HADM when compared with those who underwent submuscular placement. This must be weighed against the advantages in enhancing aesthetic outcomes, increasing intraoperative fill volume, and ameliorating capsular contracture.